The Right of Inheritance and Modern Reproductive Technologies - Lali Bagrationi (European Scientific Journal, ESJ, 2017)
The article deals with the issues related to the right of inheritance of a child born with the help of modern reproductive technologies. The paper discusses appropriate legislative amendments in the Civil Code and in the decree of the Minister of Justice on “Approval of the Registration of Civil Acts” enforcement of which will facilitate to define the rights and obligations of a child born by surrogacy and a donor’s participation.